Financial Sector Reform after the Subprime Crisis: Has Anything Happened? - Schäfer, Alexander; Schnabel, Isabel; Weder di Mauro, Beatrice (Review of Finance, 2016)
Abstract We analyze the reactions of stock returns and the spreads of credit default swaps (CDS) of banks from Europe and the USA to four major regulatory reforms in the aftermath of the subprime crisis, employing an event study analysis. Contrary to public perception, we find that financial markets indeed reacted to the structural reforms enacted at the national level. The reforms succeeded in reducing bail-out expectations relative to the post-bail-out period, especially for systemic banks. The strongest effects were found for the Dodd–Frank Act and in particular for the Volcker rule. Bank profitability was affected in all countries, showing up in lower equity returns.